The influence of hyperglycemia during radiotherapy on survival in patients with primary glioblastoma. (1st February 2016) - Adeberg, Sebastian; Bernhardt, Denise; Foerster, Robert; Bostel, Tilman; Koerber, Stefan Alexander; Mohr, Angela; Koelsche, Christian; Rieken, Stefan; Debus, Juergen
Abstract : Background and purpose. Metabolism in tumor cells depends mainly on glycolysis and thus hyperglycemia has been shown to influence tumor properties in various tumor entities. In this retrospective study we set out to determine if hyperglycemic serum levels during radiation therapy impact patient survival and progression patterns in primary glioblastoma (GBM). Material and methods. We retrospectively analyzed glucose serum levels, survival and progression patterns on magnetic resonance imaging (MRI) in 262 GBM patients receiving radiation therapy. Hyperglycemia was classified as mild (> 180 mg/dL) or excessive (≥ 300 mg/dL), and isolated (one hyperglycemic event) or persistent (≥ 3 hyperglycemic events). The multivariate Cox proportional hazards ratio was used to assess the influence of cofactors on survival. Results. Persistent mild (HR = 2.23; p < 0.001) and excessive hyperglycemia (HR = 2.51; p < 0.001) were associated with a decrease in overall survival rates, even when considering the covariate corticosteroid therapy. Here metabolic imbalances did not affect the progression-free interval (p = 0.402), the occurrence of distant (p = 0.587) and multifocal progression (p = 0.445). Conclusion. Our findings support the theory that hyperglycemia during radiation therapy in GBM patients is an unfavorable prognostic cofactor for survival and is detrimental to the survival rates independent of corticosteroid therapy. However, no significant effects of hyperglycemic metabolism on the progression-free interval and recurrence patterns were found.